Strategic curriculum Review framework using House of Quality (HOQ) - Mohd Abbas, Norliana; Abd Razak, Azli; Adull Manan, Nor Fazli; Mohd Anuar, Mohd Afzan; Saad, Idris (2025)
Curriculum review (CR) is a periodic process for an academic program. In higher education, the process is conducted once every 3-5 years for the purpose of continual improvement, addressing feedback from stakeholders and compliance with relevant standards and policies. House of Quality (HOQ) is a graphical presentation that integrates key information to support decision making and is widely used in the manufacturing industry. There is a need for a structured framework in addressing the CR process due to complexity and multitude of variables involved. This work proposes a framework to support the CR process utilizing the HOQ. The process began with the identification of a theme for the new CR. Then, potential courses were brainstormed and organized by using an affinity diagram which clustered the courses into (i) four main academic areas and (ii) the four academic years of the program. Each academic year was then assigned a theme to represent the level of the courses offered. A double relationship diagram was employed to determine (i) the interrelationship among the proposed courses and (ii) the alignment with sustainable criteria and the technical requirement. These elements were then incorporated into the HOQ. A matrix analysis together with correlation matrix were then calculated. A competitive evaluation and benchmark performance were conducted by comparing to one (1) local university and one (1) international university, respectively. Through this framework, the most influential variables in the CR process were identified and benchmarked, enabling comprehensive analysis of the strengths of the new curriculum relative to the selected institutions.